Objectification of women and the pathosformel of the male gaze in Iracema - uma transa amazônica - Frota Reinaldo, Gabriela (2024)
Amid a precarious and little-known Brazilian reality in the Amazon region, faced with the hostility of nature and the ruthless exploitation of men, this work seeks to think about how women are objectified in Iracema - uma transa amazônica (1974) based on the work of feminist film theorists and the concept of scopophilia developed by Sigmund Freud and used by them. It also seeks, based on the misogynistic and patriarchal reality with which Iracema is treated throughout the film; to think of this work as a survival of the male gaze and objectifying process that John Berger (2022) highlighted in the 1970s using 15th-century European paintings for advertising campaigns. We use the concept of survival from the reflections of Aby Warburg regarding the concept of Nachleben, a term that is difficult to translate and which is related, with his reflections on the formula of pathos or pathosformel, to thinking about a pathosformel of the male gaze in Iracema - uma transa amazônica. This allows us to highlight the significance of the creation of movements and manifestations of criticism and resistance to the massive and industrial preponderance of this model of production of the gaze, not only in the period in which this movie was produced and transmitted but also in our contemporary times, 50 years later. This makes it possible to show how in the arrival of social networks, masculine and objectifying ways of constructing the gaze can be found in various digital media, as well as manifestations of criticism, resistance, and counterproposals that bring together other ways of constructing the gaze; the look of the camera.